Correlations Between Hardness of Food and Craniodental Traits in Nine Myotis Species (Chiroptera, Vespertilionidae) - Ghazali, M.; Dzeverin, I. (Вестник зоологии, 2013)
We studied 8 skull and 42 dental characters in nine Myotis species (M. myotis, M. blythii, M. bechsteinii, M. dasycneme, M. emarginatus, M. nattereri, M. daubentonii, M. brandtii, M. mystacinus) to analyze correlations between hardness of food and skull and dental traits. Contrary to the common bat pattern, Myotis that are specialized on hard-shelled dietary items tend to have relatively narrow skull and long tooth rows. The dentition of durophagous Myotis is composed by relatively enlarged second and reduced third molars.